Exploring the Collaboration Potential Between Indonesia's Halal Industry and the K-Pop Entertainment Industry in Enhancing Halal Product Exports - Adi Tri Pramono; Andi Martina Kamaruddin; Muhammad Iqbal (Universitas Islam Negeri Alauddin Makassar, 2024)
The collaboration potential between Indonesia's halal industry and the K-Pop entertainment industry offers a strategic opportunity to boost halal product exports. As K-Pop's popularity grows in Indonesia, this cultural trend could effectively promote Indonesian halal products on a global scale. This study employs a quantitative approach, using a survey method with 400 respondents, including halal industry stakeholders, marketing experts, and K-Pop fans in Indonesia. Data were gathered through structured questionnaires measuring perceptions and interests regarding collaboration. The analysis, using descriptive statistics and linear regression, reveals a significant positive correlation between K-Pop's popularity and consumer interest in halal products endorsed by K-Pop idols. Additionally, strategic collaboration with the K-Pop industry is shown to increase consumer purchase intentions for Indonesian halal products, contributing to export growth. suggest that integrating K-Pop into halal product marketing strategies could effectively expand market reach and enhance the global competitiveness of Indonesia's halal industry.